PENGARUH KOMUNIKASI ORGANISASI TERHADAP GAYA KEPEMIMPINAN LURAH MILENIAL DI KOTA AMBON - Amelia Tahitu; Alex Robert Tutuhatunewa; Vina Maria Fadirubun (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
Quantitative research can be interpreted as a method based on the philosophy of positivism, used to research certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical with the aim of testing predetermined hypotheses. . included in quantitative methods are experimental and survey methods, therefore the method used in this research is a survey method, to obtain data from certain natural (not artificial) places, but researchers carry out treatments in collecting data, for example by distributing questionnaires, tests, structured interviews and so on. Based on the results of the research above with 40 respondent answers and 27 indicators or questions, the researcher obtained the results using several tests including validity tests to correct and find out whether each statement in the questionnaire with the number of each variable from the test results was known, that the calculation results are valid. Then the researcher continued with the reliability test, t test (partial), f test (simultaneous), knowing that the independent variables together had a significant effect on the dependent variable, thus from these two data tests the hypothesis was accepted. This means that Organizational Communication has an impact on the Leadership Style of Millennial Village Heads in Ambon City. Next, the researcher used a simple regression test and coefficient of determination test to calculate the magnitude of the impact of the independent variable on the dependent variable, so it can be shown that the percentage impact of organizational communication is 42.3% while the remaining 47.7% is influenced by other indicators. Variable Y is the leadership style of millennial village heads with indicators namely: democratic style, bureaucratic style have a significant effect on variable X so that the hypothesis results are accepted.